The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1155/2023/8677521
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Social Media on Young People’s Mental Health: Development and Validation of the Social Media-Induced Tendency Scale

Abstract: Social media use has been linked to adverse health outcomes such as depression. To facilitate interventions, understanding the varied causes of depression is necessary. The authors developed a social media-induced depression tendency (SMIDT) scale for use with young people and aimed to validate it for young people in Nigeria. The study was conducted in three parts using an online survey (Google Forms) with purposive sampling targeting young people. Study 1 was an exploratory study that developed the SMIDT scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These circumstances have illuminated the need to grasp factors such as EI that bolster resilience, especially given the specific challenges often faced by African adolescents (e.g., emotional and physical conflicts, infectious diseases, and physical and sexual abuse) that could influence mental health (Dorado Barbé et al, 2021;Kuhlman et al, 2021;Ugwu et al, 2023). Understanding the interplay between EI and trauma offers insights for interventions that enhance resilience and long-term emotional well-being.…”
Section: Introductionmentioning
confidence: 99%
“…These circumstances have illuminated the need to grasp factors such as EI that bolster resilience, especially given the specific challenges often faced by African adolescents (e.g., emotional and physical conflicts, infectious diseases, and physical and sexual abuse) that could influence mental health (Dorado Barbé et al, 2021;Kuhlman et al, 2021;Ugwu et al, 2023). Understanding the interplay between EI and trauma offers insights for interventions that enhance resilience and long-term emotional well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Through misinformation and fake news, the media, for example, social media, play key roles in sensitising mental health issues among young adults, such as stress, anxiety, depression, mental health shame, stigma, and suicide [45][46][47]. Although social media has been linked to poor mental health among young adults in Nigeria [48,49], it can serve as a means for promoting mental health and well-being through health-promotion campaigns [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…Although direct studies linking SI and IA are lacking, related constructs such as emotional intelligence (EI) have been inversely associated with IA, suggesting that individuals with lower EI may be more prone to higher levels of IA [ 19 ]. In addition, researchers [ 20 ] have found that individuals with poor social skills or who experience a high level of interpersonal anxiety may be susceptible to cyberspace relationships [ 21 ]. This suggests that individuals with low social intelligence could be predisposed to greater IA levels than people with higher SI.…”
Section: Introductionmentioning
confidence: 99%